The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00167-012-2089-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for unstable distal clavicle fractures (Neer 2) with locking T-plate and additional PDS cerclage

Abstract: Purpose The purpose of the current study was to assess the clinical and radiological results after locking T-plate osteosynthesis with coracoclavicular augmentation of unstable and displaced distal clavicle fractures (Neer type 2). Methods Thirty patients, treated between January 2007 and January 2010 were followed up after a median followup time of 12.2 months (range 4.7-37.2). The Constant and DASH scores were used to evaluate the clinical outcome, and anterior-posterior and 30°cephalic view radiographs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 36 publications
3
28
0
2
Order By: Relevance
“…We observed a high rate of union (97.2 %) and a low complication rate (5.6 %) using this treatment strategy. Our results were compatible with the results of literature [14][15][16][17][18][19][20] and only one nonunion occurred in six months in our series. Although the functional shoulder score showed no difference between the distal clavicular locking plate and clavicular hook plate groups, the distal clavicular locking plate group had greater ability to return to their previous work in three months after surgery compared to the clavicular hook plate group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed a high rate of union (97.2 %) and a low complication rate (5.6 %) using this treatment strategy. Our results were compatible with the results of literature [14][15][16][17][18][19][20] and only one nonunion occurred in six months in our series. Although the functional shoulder score showed no difference between the distal clavicular locking plate and clavicular hook plate groups, the distal clavicular locking plate group had greater ability to return to their previous work in three months after surgery compared to the clavicular hook plate group.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have reported excellent results of distal clavicle fractures treated with locking plate [14,15,17,26,29,30]. Treatment for unstable distal clavicle fractures using a locking T-plate and a CC PDS (polydioxansulfate) cerclage can provide good and reliable clinical results and a 100 % union rate [16]. Internal fixation with a 2.4-mm distal clavicle T-plate, coracoclavicular ligament repair, and augmentation of the ruptured coracoclavicular ligaments using a PDS cord holds anatomic reduction and allows early full mobilization of the injured shoulder girdle to accomplish a fast return of shoulder function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4,6,7,9,20 The techniques used can be classified according to the plane of fixation into: 1) horizontal fixation in the form of K-wires, either transarticular across the acromioclavicular joint or extraarticular, using a hook plate 15 ; or locking plates; 2) vertical fixation in the form of coracoclavicular screws, 21 suture anchors 17 or tension band wires 4 ; and 3) a combination of both horizontal and vertical fixation in the form of plates augmented with tension bands or coracoclavicular screws. 10,[22][23][24] In this study we used the UCAC loop for acute distal clavicle fractures, and achieved excellent results with no major complications. This simple technique produced anatomical reduction and provided adequate fixation to hold the medial clavicle in proximity to the lateral fragment in order to achieve union.…”
Section: Discussionmentioning
confidence: 98%